Menu Close

Question-128458




Question Number 128458 by SLVR last updated on 07/Jan/21
Commented by BHOOPENDRA last updated on 07/Jan/21
Givenf(f(1))=0,f(f(2))=0  i.e equation f(x)=0  has two root f(1)andf(2)  f(1)+f(2)=−α and f(1).f(2)=β  so 5+3α+2β=−α  and (1+α+β)(4+2α+β)  ⇒2α+β=−(5/2)  ⇒(1−(5/4)−(β/2))(4−(5/2))=β  ⇒β=−(3/2)  ∴ f(0)=β=−(3/2)
Givenf(f(1))=0,f(f(2))=0i.eequationf(x)=0hastworootf(1)andf(2)f(1)+f(2)=αandf(1).f(2)=βso5+3α+2β=αand(1+α+β)(4+2α+β)2α+β=52(154β2)(452)=ββ=32f(0)=β=32

Leave a Reply

Your email address will not be published. Required fields are marked *